Traveling Islamophobia in the Global South: - Ashraf Kunnummal & Farid Esack (Journal for the Study of Religion)
Malala Yousafzai (1997-) became an international icon after Pakistan-based Tehrik-i-Taliban militants attacked her on her way to school on October 9, 2012. In the following days, the global media gave extensive coverage to the attack from multiple narrative positions. This article argues that the traveling of Yousafzai as an image of a Muslim girl’s right to education was instru-mentalized in the context of Kerala, South India, to deny Muslims the right to political agency. By analyzing the traveling of Islamophobia in the Global South, this article shows how the gender-based stereotypes of Islamic politi-cal subjectivity were reproduced through the figure of Yousafzai. By looking into the particularities within the Global South, this article argues that Islamo-phobia as a discourse is now part of a global economy within which the threat of Muslim subjectivity is applied in unique ways.